The Book Review of “Form and Creation in Iranian Music” - Ehsan Zabihifar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “Form and Creation in Iranian Music” has been written and edited based on one of the academic courses of Iranian music, and at least because of the lack of references in this field, this book is considered as a reference and rich source. Its critique has been done with the aim of developing the domains of study in this field. The source of the major theoretical backgrounds of the book is the personal experiences and ideas of the author, as a well-known figure in this field. Using numerous and various examples related to the titles and issues, as well as the content of the last chapter about the genres in Iranian music, can be considered as the highlights. The incoherence of the contents in certain titles, not presenting enough explanations of some expressions, and ambiguity when using certain specialized vocabulary can be counted as weaknesses of the work.